Leprosy Trophic Ulcer Management - Karna, Ni Luh Putu Ratih Vibriyanti (Review of Primary Care Practice and Education, 2025)
Background: Leprosy is a chronic granulomatous infection caused by Mycobacterium leprae, also a polymorphic disease with a wide range of neurocutaneous manifestations. Unfortunately, delayed diagnosis and treatment are still an issue in endemic poor resource settings and in non-endemic countries due to global migration. Ulcer is not a common feature in leprosy patients, except during reactional states, Lucio’s phenomenon (LP), or secondary to neuropathies. Objective:To study the treatment options to manage leprosy trophic ulcer. Method: The Google-scholar, Science-Direct database, and ResearchGate from 2010 until September 2023 were searched using the keywords “leprosy ulcer”, “leprosy trophic ulcer”, “plantar leprosy ulcer”, and “leprosy ulcer management.” All available cohort studies, case-series, case-reports, and expert reviews were included with an emphasis on leprosy trophic ulcer management. Results: The trophic ulcer evolves initially from a trauma/deep fissure/callosity or tenderness over pressure-bearing areas of palms and soles. Anesthesia of the foot is the central factor in the pathogenesis of plantar ulcer. Sufficient rest for a simple ulcer is essential for ulcer healing. Topical treatment to promote wound healing includes phenytoin, zinc oxide, platelet-rich plasma (PRP), platelet-rich fibrin (PRF), and hydrocolloid dressing. Various surgical methods are available for management of plantar ulcers, including skin grafts and different types of flaps. In primary care settings, early detection, patient education, and self-care practices are essential in preventing severe ulcerations and recurrence. A clinical sign that can be suspected is the stage of threatened ulcer, called the pre-ulcerative with aseptic inflammation, usually occurring under a joint or a bony prominence of the foot and characterized by edematous lesions. Initial management in primary care including wound care and protection, limiting mobility, and reducing heavy loads on the wound area, especially in the lower extremities. Conclusion: Leprosy trophic ulcer management includes sufficient rest, topical treatment to promote wound healing, and various surgical methods.